A Living Biobank of Breast Cancer Organoids Captures Disease Heterogeneity - Sachs, Norman; de Ligt, Joep; Kopper, Oded; Gogola, Ewa; Bounova, Gergana; Weeber, Fleur; Balgobind, Anjali Vanita; Wind, Karin; Gracanin, Ana; Begthel, Harry; Korving, Jeroen; van Boxtel, Ruben; et al. (Cell, 2018)
Breast cancer (BC) comprises multiple distinct subtypes that differ genetically, pathologically, and clinically. Here, we describe a robust protocol for long-term culturing of human mammary epithelial organoids. Using this protocol, >100 primary and metastatic BC organoid lines were generated, broadly recapitulating the diversity of the disease. BC organoid morphologies typically matched the histopathology, hormone receptor status, and HER2 status of the original tumor. DNA copy number variations as well as sequence changes were consistent within tumor-organoid pairs and largely retained even after extended passaging. BC organoids furthermore populated all major gene-expression-based classification groups and allowed in vitro drug screens that were consistent with in vivo xeno-transplantations and patient response. This study describes a representative collection of well-characterized BC organoids available for cancer research and drug development, as well as a strategy to assess in vitro drug response in a personalized fashion.